Corneal latency and transmission of herpes simplex virus-1. (January 2011) - Farooq, Asim V; Shukla, Deepak
The transmission of herpes simplex virus (HSV)-1 by corneal transplantation has rarely been reported. It is believed that these cases have resulted either from reactivated virus traveling from the trigeminal ganglion to the cornea or from latent HSV-1 in the donor cornea itself. Studies of long-term viral presence in corneal tissue have sought to determine whether there is evidence of true non-neuronal latency, although there are problems in its definition. Recent studies provide new insights into neuronal latency, while similar HSV-1 gene regulation in the cornea may implicate corneal latency in pathophysiology and as a potential risk for transplant recipients. This issue has led to concerns over eye banking, which currently screens for other infectious agents but not HSV-1. Here we review the literature regarding corneal latency and the transmission of HSV-1.